An updated list of Serbian diatom flora: new recorded taxa - Vidaković, Danijela P.; Jakovljević, Olga S; Predojević, Dragana D.; Radovanović, Sanja M.; Subakov-Simić, Gordana V.; Lazović, Vladimir M.; Krizmanić, Jelena Ž. (Archives of Biological Sciences, 2018)
Diatoms are a widespread group of organisms with well-known ecological preferences. Knowledge of their diversity is of great importance for assessing the environmental status of different aquatic ecosystems. The present study was based on 55 different localities that included rivers, streams, channels, accumulations and salt marshes throughout Serbia. The results of this study expanded the diatom checklist by 80 taxa, including two new recorded genera (Fistulifera and Microfissurata) for Serbia. The data were obtained by combining light microscopy (LM) and scanning electron microscopy (SEM) that provided reliable identification, which is very important in diatom diversity studies. https://doi.org/10.2298/ABS170606043V Received: June 6, 2017; Revised: September 15, 2017; Accepted: October 13, 2017; Published online: November 11, 2017 How to cite this article: Vidaković DP, Jakovljević OS, Predojević DD, Radovanović SM, Subakov-Simić GV, Lazović VM, Krizmanić JŽ. An updated list of Serbian diatom flora: new recorded taxa. Arch Biol Sci. 2018;70(2):259-75.